Policy advocacy to enable administrative data linking: building a civil society coalition - Lenczner, Michael; McPhedran Waitzer, Jonathan (International Journal of Population Data Science, 2018)
Introduction Administrative data linking holds tremendous promise for improving understanding of social problems, enhancing service delivery, and revolutionizing impact evaluation in Canada. Embracing this opportunity at scale requires navigation of significant technical and policy challenges. The greatest challenge, though, may be a lack of political will. Objectives and Approach The nonprofit sector is uniquely positioned to advocate for a strong political commitment to linked administrative data. As a sector, it could directly benefit from that data for impact evaluation and for advocacy. It is also closest to the people who are most likely to be negatively impacted by the resulting surveillance and stigmatization. We are building a network of social service organizations, foundations, and advocacy groups to explore the possibility of creating a shared policy agenda. We’ve developed a coalition model that engages these unequally resourced stakeholders on equal footing - with the goal of enabling fully-informed and equitable participation. Results This coalition is working to develop a set of conditions for increased administrative data linking that reflect the shared interests of funders, service providers, advocacy groups, and beneficiary communities. We are also researching the legislative and policy changes required to enable that desired outcome. In developing this agenda, and bringing it to government, we hope to provide the social license (and public pressure) required to create an enabling policy environment for increased data linking in Canada. Beyond developing a shared agenda, this initiative also aims to deliver long-term outcomes involving increased data policy literacy among Canadian nonprofits. This coalition represents collaborative infrastructure to enable ongoing, coordinated input from the nonprofit sector on key questions of data governance and policy. Conclusion/Implications This equity-focused, multi-stakeholder coalition approach to digital policy development represents a significant innovation in public engagement. We’re excited to share our process and key learnings with conference participants with hopes of receiving expert feedback while inviting key allies to engage in this emerging initiative.